Analysis Of Character Value in Local Wisdom in Kompang Game at 002 Teluk Uma Elementary School, Tebing District, Karimun - Delina Octarainy; Zufriady; Adi Putra, M. Jaya (Yayasan Thaifah Manshurah Pekanbaru, 2024)
The progress of the era in the globalization era has significantly shifted the original local cultural values of Indonesia, our various efforts for the next generation must maintain the existing traditions, Tanjung Balai Karimun is a Malay land that still preserves the traditional game of kompang. With the Kompang game, we can see the characters in the students. Character is a value that has existed since humans were born which is permanent and can also experience changes in the humans themselves, which can be seen through their actions or behavior. Strengthening the Pancasila student profile focuses on cultivating character and abilities in everyday life that are instilled in individual students through school culture, intra-curricular and extra-curricular learning, project to strengthen Pancasila student profiles and work culture. The purpose of this study is to find out what character values exist in local wisdom in the game Kompang in elementary school. The research method used is a qualitative method. In this study, three data analysis techniques were used, namely (1) data reduction (2) data presentation (3) conclusion drawing/verification/conclusion. Based on the results of this study it can be found that the strongest character values among students who take part in this Kompang game extracurricular are (Faith, piety to God Almighty and noble character, Global Diversity, and Mutual Cooperation The research method used is a qualitative method. In this study, three data analysis techniques were used, namely (1) data reduction (2) data presentation (3) conclusion drawing/verification/conclusion. Based on the results of this study it can be found that the strongest character values among students who take part in this Kompang game extracurricular are (Faith, piety to God Almighty and noble character, Global Diversity, and Mutual Cooperation The research method used is a qualitative method. In this study, three data analysis techniques were used, namely (1) data reduction (2) data presentation (3) conclusion drawing/verification/conclusion. Based on the results of this study it can be found that the strongest character values among students who take part in this Kompang game extracurricular are (Faith, piety to God Almighty and noble character, Global Diversity, and Mutual Cooperation